Hubungan Antara Rinitis Alergi dengan Kualitas Hidup pada Mahasiswa FKIK Universitas Warmadewa - Anak Agung Gede Ngurah Agung Kesumaputra; Luh Gede Pradnyawati; I Wayan Suwandara (Aesculapius Medical Journal, 2025)
Allergic rhinitis one of allergic disease that has a high prevalence in the world, 400 million people suffer from allergic rhinitis, while in Indonesia the number is 24.3% of the total population.The purpose of this study was to determine the corelation between allergic rhinitis and quality of life in students at the Faculty of Medicine and Health Sciences, Warmadewa University. The analysis of this study uses cross sectional approach. The sampling technique used random sampling and of 49 sample size.  The instruments research used the SFAR questionnaire to assess allergic rhinitis and the WHOQOL-BREF questionnaire to assess quality of life. Data processing will be carried out using SPSS with bivariate analysis. There were total of 49 respondents who met the inclusion criteria. Majority of respondents had a previous history of allergic rhinitis (93.9%) with moderate quality of life (91.8%) and the other (8.2%) with high quality of life. The enviromental doimain was recorded with a high quality of life level of 10.2%, while the lowest quality of life was in the social domain. There was no corelation between allergic rhinitis and quality of life (p = 0.582, r = 0.081). The age of the majority of students with allergic rhinitis is in accordance with the atopic march theory where allergic rhinitis reaches its peak at the age of 20-40 years. Several previous studies also found that the most common symptom of a runny nose is that the most common trigger is house dust mites which have a habitat in urban areas. However, this study did not find a corelation between allergic rhinitis and quality of life, which may be due to student factors, research instruments that cause bias, and smaller study samples.